2021
DOI: 10.3390/agronomy11091804
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pesticide Residues in Fresh Vegetables Available in Local Markets for Human Consumption and the Associated Health Risks

Abstract: Human health risks as a result of consuming pesticide residues in fresh vegetables have drawn serious attention to the scientific community, particularly in developing countries. This study analyzed country bean (Lablab purpureus L.) and eggplant (Solanum melongena L.) for widely used neonicotinoid, synthetic pyrethroid, and dithiocarbamate pesticide residues in order to ensure food safety. The analyzed vegetables contained residues of acetamiprid and cypermethrin in 17% of bean and 13% of eggplant samples, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Fresh agricultural products such as spinach ( Spinacia oleracea ) are essential to the human diet because they provide us with vitamins, minerals, glucosinolates, carotenoids, and bioactive compounds [6] . Studies reported that fresh agricultural products transported into the market were detected with high MRL of pesticides [7] . Among the pesticides, chlorothalonil is one of the most commonly used fungicides for spinach [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Fresh agricultural products such as spinach ( Spinacia oleracea ) are essential to the human diet because they provide us with vitamins, minerals, glucosinolates, carotenoids, and bioactive compounds [6] . Studies reported that fresh agricultural products transported into the market were detected with high MRL of pesticides [7] . Among the pesticides, chlorothalonil is one of the most commonly used fungicides for spinach [8] .…”
Section: Introductionmentioning
confidence: 99%
“…This crop is grown in all 64 districts and almost every village in the homestead garden in Bangladesh. Although beans are cultivated in the winter, they become a year-round crop as photo-insensitive, and summer varieties become available ( Nisha et al., 2021 ; Ahmed et el ., 2004 ; Biswas 2015 ). In Bangladesh, growers produced about 1,69,735 metric tons of country beans from 61,628 acres ( BBS, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Without the use of pesticides, there would be a 78% loss of fruit production, a 54% loss of vegetable production, and a 32% loss of cereal production (Tudi et al, 2021). However, the inappropriate use of pesticides in agriculture may result in many health problems for producers and consumers who are exposed through their handling practices (Nisha et al, 2021;Parven et al, 2021). The overall rate of pesticide contamination for tomatoes in our study (62.2%) is very high.…”
Section: Discussionmentioning
confidence: 64%